Aspectos tafonômicos da conchostracofauna (spinicaudata, crustacea) formação pastos bons (jurássico superior), Piauí, Brasil - Moura, Francisca Raiany Soares de (2022)
The Parnaíba Basin is well known for its fossil record, mainly in Paleozoic fossils, but it also has extensive fossiliferous areas from the Mesozoic. In the city of Floriano (PI) several geological units of this basin emerge, including the Jurassic Pastos Bons Formation. In the outcrop known as Fazenda Muzinho, the presence of plant fossils (vegetable cuticles), vertebrates (fish) and invertebrates (conchostraceans) was recorded. The region's paleoichthyofauna has received deserved protagonism, but recently the conchostracans have gained prominence in studies and this has motivated research to describe the species present in the place and the processes that involve their fossilization. This research analyzes the taphonomic processes of the conchostracofauna and with them we try to propose paleoenvironmental and paleoecological interpretations, suggesting which environmental factors influenced the death of these animals and the processes by which their preservation was possible. The research was carried out through fieldwork, laboratory analysis and data interpretation. Our results demonstrated the fossiliferous potential of the region, confirmed data referring to the local paleoenvironment and how the bioclasts were exposed during the fossilization events.